2010
DOI: 10.1590/s0037-86822010000200004
|View full text |Cite
|
Sign up to set email alerts
|

Análise da fonte alimentar de Panstrongylus megistus (Hemiptera, Reduviidae, Triatominae) e sua atual importância como vetor do Trypanosoma cruzi, no Estado de Minas Gerais

Abstract: INTRODUÇÃO: A pesquisa da fonte alimentar dos triatomíneos auxilia no conhecimento sobre a biologia destes insetos, inclusive para inferir-se a importância dos mesmos como transmissores do Trypanosoma cruzi ao homem. MÉTODOS: O presente estudo objetivou registrar, através da reação de precipitina, a fonte alimentar de triatomíneos provenientes de 54 municípios da região centro-oeste de Minas Gerais, assim como a infecção natural destes para flagelados semelhantes ao Trypanosoma cruzi. RESULTADOS: De julho de 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 16 publications
0
16
1
2
Order By: Relevance
“…Adults seem to disperse from there by fl ight during the warmest and most humid periods of the year, as observed in municipalities of the midwestern part of Minas Gerais ( Figure 2D) (9) . In that region, 22.5% of 416 P. megistus specimens had ingested human blood and 3.8% of specimens were positive for trypanosomatids, thus surpassing the percentage reported herein (2.7%) (10) .…”
contrasting
confidence: 63%
“…Adults seem to disperse from there by fl ight during the warmest and most humid periods of the year, as observed in municipalities of the midwestern part of Minas Gerais ( Figure 2D) (9) . In that region, 22.5% of 416 P. megistus specimens had ingested human blood and 3.8% of specimens were positive for trypanosomatids, thus surpassing the percentage reported herein (2.7%) (10) .…”
contrasting
confidence: 63%
“…This is due primarily to the transmission of Trypanosoma cruzi by Triatoma infestans, which also lives in human dwellings 29 . Thus, dogs and cats play an important role in the maintenance of the disease, in addition to other domestic and wild mammals that frequent the areas surrounding homes 3,4,12 . In the case of cats, although infection rates are low, their association with the domestic cycle is closely associated with their wandering habits 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Triatomines undergo a domiciliation process when they are forced out of their wild environments due to habitat destruction around dwellings, after which they find shelter in rural constructions [6][7][8] . In addition, the presence of domestic animals and peri-domestic constructions used for animal maintenance and breeding greatly influences the presence and transmission of parasites because they provide a permanent food source and promote contact between vectors and humans 7,[9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…B irds, although refractory to parasites, enable the maintenance of colonies and can act as population growth vectors, thereby increasing the risk of disease transmission, especially if the triatomines had previous contact with an infected mammal 61 . In an analysis of populations in the State of Minas Gerais Midwest, Villela et al 62 also found a higher level of blood feeding on birds in triatomines captured in peridomiciliary environments; however, the majority (90.4%) of individual triatomines fed on only one source (bird and others species). The same authors showed that 44% of infected bugs had this source.…”
Section: Discussionmentioning
confidence: 96%